2013
DOI: 10.1371/journal.pone.0071082
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Acyl Acids Attenuate the Unfolded Protein Response in Tunicamycin-Treated Neuroblastoma Cells

Abstract: Understanding how neural cells handle proteostasis stress in the endoplasmic reticulum (ER) is important to decipher the mechanisms that underlie the cell death associated with neurodegenerative diseases and to design appropriate therapeutic tools. Here we have compared the sensitivity of a human neuroblastoma cell line (SH-SY5H) to the ER stress caused by an inhibitor of protein glycosylation with that observed in human embryonic kidney (HEK-293T) cells. In response to stress, SH-SY5H cells increase the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…The authors concluded that 4-PBA protected against ER stress-induced but not mitochondriamediated cell death in this model (Qi et al, 2004). These findings are consistent with recent evidence suggesting that 4-PBA protected a neuroblastoma cell line from tunicamycin- (Zamarbide et al, 2013) and hydrogen peroxide- (Ye et al, 2014) induced UPR activation and cell death.…”
Section: The Effects Of 4-pba On Neurological Diseases and Models Of supporting
confidence: 87%
“…The authors concluded that 4-PBA protected against ER stress-induced but not mitochondriamediated cell death in this model (Qi et al, 2004). These findings are consistent with recent evidence suggesting that 4-PBA protected a neuroblastoma cell line from tunicamycin- (Zamarbide et al, 2013) and hydrogen peroxide- (Ye et al, 2014) induced UPR activation and cell death.…”
Section: The Effects Of 4-pba On Neurological Diseases and Models Of supporting
confidence: 87%
“…ER stress and autophagy are other possible mechanisms of nanoparticle-induced toxicity [7,14,15]. In our study, we did not detect any changes in mRNA or protein levels of UPR markers HSPA5 (BiP), DDIT3 (CHOP) and XBP1s [33]. Although we found PM0.5 localized in structures similar to autophagosomes or late endosomal multivesicular bodies, autophagy was not induced in the PM0.5-exposed A549 cells (as determined by LC3B and p62 protein level and CYTO-ID ® marker).…”
Section: Discussioncontrasting
confidence: 64%
“…ER stress leads to activation of genes involved in compensatory response, the UPR. We measured changes in HSPA5 (also known as binding immunoglobulin protein, BiP), DDIT3 (CHOP) and XBP1s mRNA and protein levels, representing activation of all three UPR pathways [33]. We found that, in contrast to commonly used ER stress inducers thapsigargin and tunicamycin, PM0.5 did not change mRNA levels of tested UPR-associated genes ( Figure 5).…”
Section: Induction Of Novel Toxicity Markers-early Stress Response Gementioning
confidence: 97%
“…7b, c). Tunicamycin has been reported to increase caspase-4 activity [18, 58] and reduce the viability of SH-SY5Y cells [16, 61]. We therefore measured cell viability of the cultured SH-SY5Y cells using CCK-8, a widely used assay that can sensitively measure the viability of a variety of cultured cells including SH-SY5Y cells [10, 56].…”
Section: Resultsmentioning
confidence: 99%